2018
DOI: 10.2337/db17-0946
|View full text |Cite
|
Sign up to set email alerts
|

Modest Decreases in Endogenous All-trans-Retinoic Acid Produced by a MouseRdh10Heterozygote Provoke Major Abnormalities in Adipogenesis and Lipid Metabolism

Abstract: Pharmacological dosing of all--retinoic acid (atRA) controls adiposity in rodents by inhibiting adipogenesis and inducing fatty acid oxidation. Retinol dehydrogenases (Rdh) catalyze the first reaction that activates retinol into atRA. This study examined postnatal contributions of Rdh10 to atRA biosynthesis and physiological functions of endogenous atRA. Embryonic fibroblasts from heterozygote hypomorphs or with a total knockout exhibit decreased atRA biosynthesis and escalated adipogenesis. atRA or a retinoic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 50 publications
(50 reference statements)
3
55
0
Order By: Relevance
“…Recent studies reported by Yang et al (2018) are consistent with this early literature (Bost et al, 2002) regarding the effects of retinoic acid on mouse ES cell commitment to the adipocyte lineage. Yang et al (2018) report that modest decreases in endogenous all-transretinoic acid concentrations in male and female mice heterozygous for the Rdh10 gene were associated with metabolic abnormalities including effects on glucose and insulin sensitivity and adipogenesis. In vitro investigations involving the use of mouse embryonic fibroblasts (MEFs) identified all-trans-retinoic acid levels to be diminished by approximately 50% in cells heterozygous for the Rdh10-null allele.…”
Section: B Vitamin a Vitamin A-related Proteins And Adipose Biologysupporting
confidence: 85%
See 2 more Smart Citations
“…Recent studies reported by Yang et al (2018) are consistent with this early literature (Bost et al, 2002) regarding the effects of retinoic acid on mouse ES cell commitment to the adipocyte lineage. Yang et al (2018) report that modest decreases in endogenous all-transretinoic acid concentrations in male and female mice heterozygous for the Rdh10 gene were associated with metabolic abnormalities including effects on glucose and insulin sensitivity and adipogenesis. In vitro investigations involving the use of mouse embryonic fibroblasts (MEFs) identified all-trans-retinoic acid levels to be diminished by approximately 50% in cells heterozygous for the Rdh10-null allele.…”
Section: B Vitamin a Vitamin A-related Proteins And Adipose Biologysupporting
confidence: 85%
“…Loss of Aldh1a1 expression was not found to affect retinoic acid synthesis when the MEFs were treated with retinol. Yang et al (2018) conclude that actions of ALDH1A1 not related to its role in vitamin A metabolism likely account for the effects of this enzyme is causing resistance to weight gain. The authors further noted that ALDH1A1 catalyzes other important oxidizations within cells including those of 4-hydroxy-2-nonenal and acrolein, two toxic aldehyde products formed through lipid peroxidation (Makia et al, 2011).…”
Section: Aldh1a1 Actions In Adipocytes and Obesity-aldh1a1 (Raldh1)mentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, a recent study in mice heterozygous for Rdh10 knockout found increased steatosis on a high-fat diet despite only a modest decrease in hepatic RA. (45) This suggests unique substrate specificity and is consistent with retinoids being the substrate for HSD17B13. Ongoing in vivo experiments are aimed at confirming these findings.…”
Section: Discussionsupporting
confidence: 70%
“…We are aware that retinoid plasma concentrations per se may not necessarily have a dramatic biological impact. However it has been demonstrated that very subtle changes in the tissue retinoid content can have substantial functional effects, particularly on the transcriptional level [ 32 ]. It is also possible that longer cold challenges may have even more pronounced effects on retinoid metabolism and biological outcomes, such as WAT browning.…”
Section: Discussionmentioning
confidence: 99%